Risk management system for the monitoring and control of a small lettuce greenhouse - Juan Guzmán; Juan Goyeneche; William Mosquera; Roberto Ferro; Jhon Monje; Edgar Aguirre (International Journal of Advances in Applied Sciences, 2022)
The management of agricultural risks is a scenario that allows knowing the probable factors that can affect a crop, knowing the variables allow designing control and mitigation of projects in case of any affectation, failure to do so may cause loss of production, the objective This research was the design and construction of a monitoring system for greenhouses that would allow to carry out a small-scale control of the environment, through knowledge of the behavior of the different agroecological variables that intervene in the process, allowing to generate different scenarios For the control of the different variables of nutrition, irrigation, and lighting, it was possible to carry out a set of experiments that showed that the system allows controlling the production in the established time, as well as the effect of the control on the quality of the vegetables.